BOTANICAL CHARACTERISTICS OF BETA VULGARIS L. V. CRASSA (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article provides information about the botanical characteristics of the beetroot plant (root, stem, leaf, flower) and the requirements of these plants for factors such as light, heat, moisture, and soil